MORAL OBJECTIVISM AS A BASIC FOUNDATION AND STANDARD OF HUMAN CONDUCT - Anweting Kevin Ibok (Social Landscape Journal, 2020)
Generally acknowledged accounts of human action firmly recommend that actions must be identified from the first individual point of view, i.e. from the perspective of the reasons that motivate an agent. To this there have been bunches of contention as regards to the standard of human conduct in general. The discussion in which moral disagreement has received most attention is metaethical and concerns the objectivity of ethics. The subjective hypothesis contends that the standard for human action is from a subjective view. Then again some other few speculations have guaranteed that ethical objectivism decides the rightness or unsoundness of our actions. This paper joins the list of long debates on the subject matter. The paper summits that moral objectivism is a basic foundation and determines the rightness or wrongness of our actions corresponding to other theories.